2015
DOI: 10.7183/1045-6635.26.3.362
|View full text |Cite
|
Sign up to set email alerts
|

Settlement Organization and Architecture in Late Intermediate Period Chachapoyas, Northeastern Peru

Abstract: Chachapoya societies that lived on the forested eastern slopes of the Andes in northern Peru between A.D. 1000 and 1450 remain largely absent from broader narratives of the Andean Late Intermediate period (LIP). This paper argues that environmentally deterministic frameworks and lingering Inka biases have led scholars to problematically isolate Chachapoyans from their highland contemporaries. This work reviews three aspects of Chachapoya built environments—settlement patterning, internal organization, and arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 26 publications
0
22
0
2
Order By: Relevance
“…In fact, the cultural evidence points to the vital role of the societies in this area, as mediators of various cultural interaction spheres since very ancient times, and also to their importance in the formation and transformation of complex societies (Church and von Hagen, 2008;Guengerich, 2015). We are aware of the difficulties in assessing whether this distinct pattern reflects very early genetic signatures or the action of different evolutionary forces through time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the cultural evidence points to the vital role of the societies in this area, as mediators of various cultural interaction spheres since very ancient times, and also to their importance in the formation and transformation of complex societies (Church and von Hagen, 2008;Guengerich, 2015). We are aware of the difficulties in assessing whether this distinct pattern reflects very early genetic signatures or the action of different evolutionary forces through time.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic profile of the Chachapoya indicates that populations that developed in "intermediate ecological regions" have a complex genetic composition which has been influenced by their position with regard to other civilizations in the northeast Andes. In fact, the cultural evidence points to the vital role of the societies in this area, as mediators of various cultural interaction spheres since very ancient times, and also to their importance in the formation and transformation of complex societies (Church and von Hagen, 2008;Guengerich, 2015). Studies of extinct and extant populations in similar transitional zones have also found complex genetic configurations with high levels of genetic diversity (Casas-Vargas et al, 2011;Corella et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Las residencias al interior poseen planta subcircular de entre 4 m y 5 m de diámetro y la cerámica observada en superficie recuerda a los estilos locales del IT. Tanto el material superficial como la distribución y disposición de este sector, una colina defendida por muros perimétricos conteniendo viviendas circulares, nos hace pensar en una clásica ocupación del IT (Arkush 2011;Guengerich 2015;Parsons et al 1997). Si bien no se ha realizado un análisis intrasitio detallado de la arquitectura en este sector, es aparente el uso del mismo tipo de técnica constructiva que en el sector B (pircado) pero con una menor calidad en la mampostería, lo que podría explicar la mala conservación de las estructuras en el sector D en comparación con el sector B.…”
Section: El Sector Dunclassified
“…The eastern slopes of the Peruvian Andes (also known as the montaña or ceja de selva-the "eyebrow of the jungle") are a region in which airborne lidar holds a great deal of promise for mapping previously un-surveyed archaeological landscapes and capturing new dimensions of variability within them. Decades of excavations and pedestrian reconnaissance have demonstrated that the montaña has a deep history of human occupation and that late Prehispanic population sizes were, in many areas, substantially larger than those found in the region today (Bonavia 1981;Church 1996;Church and Von Hagen 2008;Clasby 2014;Guengerich 2015;Le Moine and Raymond 1987;Raymond 1992;Schjellerup 2003). As population declined after the Spanish invasion due to colonial violence, disease, and migration, many settlements, terracing systems, and grazing lands were abandoned, and tropical forest vegetation recolonized landscapes that had formerly been the sites of intensive economic exploitation and habitation.…”
Section: Introductionmentioning
confidence: 99%